The Antibacterial Effects and Biosolubility of L-Histidine-Supported Zinc Oxide Nanoparticles, Produced via Green Synthesis Using Orange (Citrus sinensis) Peel, in an In vitro Poultry Digestive System - Sahın, Emre; Genç, Aydın; Şahin, Saliha Bediz; Karakoç, Şirvan (My University, 2026)
In this study, the production of zinc oxide nanoparticles (ZnO-NPs) in various forms using the green synthesis method with orange peel was aimed at reducing environmental mineral pollution and enhancing the bioavailability of mineral supplements used in poultry nutrition. Subsequently, the effects of these nanoparticles on the in vitro poultry digestive system were investigated. The characterization of the synthesized nanoparticles was performed using UV-VIS spectroscopy, FT-IR spectroscopy, SEM, and EDX analysis. The results demonstrated that ZnO-NPs and His-ZnO-NPs possessed smaller particle sizes and that their antibacterial activities increased compared to bulk ZnO. Especially compared to bulk ZnO, His-ZnO-NP was found to be effective against pathogenic bacteria, such as E. coli and S. Enteritidis, in the in vitro poultry digestive system (P <0.05). On the other hand, although His-ZnO-NPs exhibited higher biosolubility than bulk ZnO and ZnO-NPs, the commercial ZnO-NPs showed the highest Zn biosolubility (P<0.05). This study revealed that histidine-supported ZnO-NPs, produced via the green synthesis method using orange peel extract, have the potential to be used as an alternative in poultry nutrition. However, in vivo studies should be performed to demonstrate the practical applications of this technology.
Keywords: Nanobilim ve Nanoteknoloji; Veterinerlik